The Encyclopedia of Murder and Mystery - Murphy, B. author. aut Link
XIV, 543 p.
Keywords: Bruce Murphy's Encyclopedia of Murder and Mystery is a comprehensive guide to the genre of the murder mystery that catalogues thousands of items in a broad range of categories: authors, titles, plots, characters, weapons, methods of killing, movie and theatrical adaptations. What distinguishes this encyclopedia from the others in the field is its critical stance.